Mental Health Symptoms in Relation to Socio-Demographic Characteristics and Lifestyle Factors among Nursing Collegians at Baghdad University - Shahad Nasret Abdown, Hassan Ali Hussein, (Pakistan Journal of Medical & Health Sciences, 2022)
Background :Mental illnesses have spread very widely in world, especially in recent years, and their causes are multiple and complex, including the lifestyle in general, and the lack of commitment to a healthy diet, lack of exercise regularly, or lack of adaptation to stress and psychological pressures, and a significant lack of sleep, which is replaced by staying up for periods of time. In addition to other factors that we will discuss in the research and according to research, the rate of prevalence of mental illness among university students is 75% who have at least one mental illness. Objective: To assess mental health among nursing collegians at Baghdad university, and to find-out the relationship between mental health symptoms of nursing students and their socio-demographic characteristic. Methodology: The study was conducted in 2021/2022 and included 171 participants representative of the Iraqi nursing student’s population. Lifestyle factors were assessed via electronic questionnaire and included frequency of physical and mental activity, alcohol consumption, smoking, as well as circadian and social regularity. Outcome variables were depression, anxiety, stress and satisfaction with life Result: There is high significant relationship between Lifestyle behavior and mental health among the nursing collegians as seen with strong positive correlation at p-value= 0.001 Conclusion: Mental health among nursing collegians at Baghdad university were fair, and there is no relationship between mental health symptoms of nursing students and their socio-demographic characteristic.